Enforcement of Asn Discipline Laws Based on The Online Personnel System Application And Its Impact on Performance In The Office of The Lubuk Sikarah District, Solok City - Otong Rosadi; Iyah Faniyah; Sutrisno, Sutrisno (Journal of Law, Politic and Humanities, 2024)
This research examines disciplinary law enforcement through the Online Civil Service System (KEPO), its obstacles and impact on ASN discipline. This type of research is normative juridical supported by empirical juridical. The data used is secondary and primary data. Secondary data was obtained from document studies and primary data was obtained by interviews. The data obtained was analyzed qualitatively, presented in a qualitative descriptive manner. First research results: In general, enforcement of disciplinary law through the KEPO system for ASN at the Kantor Camat Lubuk Sikarah is less effective. Even though discipline has been enforced by reducing or cutting additional employee income in accordance with Solok Mayor Regulation Number 17 of 2022 concerning Providing Additional Income to Regional ASN Employees. Second, the obstacles in enforcing disciplinary law through the KEPO system are: a) the legal factor is still weak: regulating the presence of a 50 meter radius, b) the law enforcement factor is still reluctant, c) the server facility factor is inadequate, d) the community understanding factor ASN in Kantor Camat Lubuk Sikarah regarding KEPO, e) Cultural Factors in the work environment in Lubuk Sikarah District, ASN's culture is reticent. Another finding from the research: there are ASNs who do not yet have an Android cellphone (camera) and a stable internet network. Meanwhile, the impact of implementing or enforcing ASN disciplinary laws on ASN performance in general has relatively increased, although it is still not effective.